7(m+3)=6(m+5)-8m

Simple and best practice solution for 7(m+3)=6(m+5)-8m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(m+3)=6(m+5)-8m equation:


Simplifying
7(m + 3) = 6(m + 5) + -8m

Reorder the terms:
7(3 + m) = 6(m + 5) + -8m
(3 * 7 + m * 7) = 6(m + 5) + -8m
(21 + 7m) = 6(m + 5) + -8m

Reorder the terms:
21 + 7m = 6(5 + m) + -8m
21 + 7m = (5 * 6 + m * 6) + -8m
21 + 7m = (30 + 6m) + -8m

Combine like terms: 6m + -8m = -2m
21 + 7m = 30 + -2m

Solving
21 + 7m = 30 + -2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2m' to each side of the equation.
21 + 7m + 2m = 30 + -2m + 2m

Combine like terms: 7m + 2m = 9m
21 + 9m = 30 + -2m + 2m

Combine like terms: -2m + 2m = 0
21 + 9m = 30 + 0
21 + 9m = 30

Add '-21' to each side of the equation.
21 + -21 + 9m = 30 + -21

Combine like terms: 21 + -21 = 0
0 + 9m = 30 + -21
9m = 30 + -21

Combine like terms: 30 + -21 = 9
9m = 9

Divide each side by '9'.
m = 1

Simplifying
m = 1

See similar equations:

| 2x+5-x=45-7x | | 40a+20b=1250 | | y=15-(-4) | | x^2-3x-8=-4x+4 | | -6(n-2)-1=-(4+7n) | | -11n^2=9-2n | | 54m= | | 14g-5g-5g-3G=17 | | -3-3r=-6(5+5r) | | x^2-13x+39=3 | | x^2=3x-28 | | 3x-5=7x-45 | | -33-2b=-5+8(1-b) | | 2w-w+4w+w-5w=8 | | 5x+4=2y | | 6(4m-6)=30+2m | | sin(3x)-sin(7x)=0 | | -2x+17=-6(x+1)-5 | | 3m-2m-m+m=7 | | (1-3x)(9x-7)=0 | | -10x+8y=10 | | (x+1)2=144 | | 16+4r=7r+7 | | 15s-6s-6s=18 | | -8+5a=-93 | | 9x^2+4=-77 | | 5x+6y=226.19 | | 4x^2-25x+27=-4x+7 | | 27+x=68 | | 4s-3s=4 | | 2-10i+5x=17-5yi | | 6k-3=-93 |

Equations solver categories